The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1016/s1569-4860(01)80015-2
|View full text |Cite
|
Sign up to set email alerts
|

Microbial transformations of plutonium and implications for its mobility

Abstract: The current state of knowledge of the effect of plutonium on microorganisms and microbial activity is reviewed, and also the microbial processes affecting its mobilization and immobilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…5a) indicating mobilisation and migration of Pu towards the anode, consistent with the migration of Pu as a negatively charged (anionic) complex. While the difficulty in accurately modelling element speciation (in the case here, Pu, which can co-exist in four different oxidation states, III-VI, in the same solution) in such a complex system under extreme pH gradients has been noted above, Pu is present in the soil environment mostly as hydroxides and oxides of Pu(IV) which have low solubility [23]. Surface sorption is a dominant feature of plutonium behaviour in soil systems, with strong sorption of Pu to mineral (Fe and Mn oxides, clays) and organic surfaces [24,25].…”
Section: Effect Of Soil Porewater Ionic Strength/application Of Soil mentioning
confidence: 89%
“…5a) indicating mobilisation and migration of Pu towards the anode, consistent with the migration of Pu as a negatively charged (anionic) complex. While the difficulty in accurately modelling element speciation (in the case here, Pu, which can co-exist in four different oxidation states, III-VI, in the same solution) in such a complex system under extreme pH gradients has been noted above, Pu is present in the soil environment mostly as hydroxides and oxides of Pu(IV) which have low solubility [23]. Surface sorption is a dominant feature of plutonium behaviour in soil systems, with strong sorption of Pu to mineral (Fe and Mn oxides, clays) and organic surfaces [24,25].…”
Section: Effect Of Soil Porewater Ionic Strength/application Of Soil mentioning
confidence: 89%
“…Microbial processes may also have a significant effect on the long-term behaviour and mobility of Pu (Francis, 2001;Francis et al, 2008). The oxidation state of Pu significantly affects its geochemical behaviour.…”
Section: Behaviour Of Pu In the Marine Environmentmentioning
confidence: 99%
“…Many experimental sorption studies were carried out under specific physicochemical conditions (anoxic conditions, high alkalinity, low organic content) that are difficult to extrapolate to surface soils (Moulin and Moulin, 1995;Kim et al, 1997;Kersting et al, 1999;Francis, 2001;Grigoriev et al, 2001;Artinger et al, 2002;Fjeld et al, 2003). Although current research has demonstrated some of the mechanisms governing the mobility of transuranides in soils, operational models either implicitly or explicitly use the classic coefficient, K d .…”
Section: Introductionmentioning
confidence: 99%